POPULATION PROBLEMS IN GLODALIZATION CIRCUMSTANCES - Сластенко, Е. Ф.; Кадникова, Л. В. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2015)
Demographical problems that have got a planetary character in globalization circumstances are analyzed in the article.